O ensino de artes e o meio ambiente : diálogo interdisciplinar sobre os corpos hídricos de Monte Alegre de Sergipe/SE - Mendonça, Luciana Fonseca (2020)
The water bodies in the semi-arid region of Monte Alegre de Sergipe present themselves in a dynamic and complex way that compromise the potability of water intended for human consumption and some species of animals. In the meantime, the degradation of water bodies culminates in water contamination, with the main sources of pollution being sewage (organic pollution), garbage (pollution by solid waste) and industries, whose dumping is the most polluting, due to the presence of harmful substances , in addition to other problems such as silting. In this sense, the research had the general objective of understanding the knowledge and experiences of individuals from the context of the environmental problems present in the water bodies of Monte Alegre de Sergipe. Thus, three water bodies from Monte Alegre de Sergipe in Alto Sertão Sergipano were delimited as the locus of scientific investigation. For that, the scientific method used corresponds to phenomenology based on the qualitative approach. Thus, with the intention of promoting the achievement of the proposed objectives, we elected the following methodological procedures: survey and bibliographic review; fieldwork - free and participant observations, notebook (field diary), photographic records, semi-structured interviews, whose script was guided by the understanding and impressions of individuals before the environmental phenomena present in the superficial water bodies of Monte de Alegre de Sergipe; and the construction of the technical-didactic product, the “Águas de Monte Alegre” website. For data analysis we have as a reference, the content analysis of Bardin (1977). Thus, from the perspective of ethics, the research sought to promote a dialogue for the construction of environmental knowledge and a proposal for changes in the behavior of individuals.